Italy : Toward a Growth-Friendly Fiscal Reform - Andrle, Michal; Hebous, Shafik; Kangur, Alvar; Raissi, Mehdi (Washington, D.C. : International Monetary Fund, 2018)
Published in late 2017, the Italian medium-term fiscal plan aims to achieve structural balance by 2020, although concrete, high-quality measures to meet the target are yet to be specified. This paper seeks to contribute to the discussion by (i) assessing spending patterns to identify areas for savings; (ii) evaluating the pension system; (iii) analyzing the scope for revenue rebalancing; and (iv) putting forward a package of spending cuts and tax rebalancing that is growth friendly and inclusive, could have limited near-term output costs, and would achieve a notable reduction in public debt over the medium term. Such a package could help the authorities balance the need to bring down public debt and, thus, reduce vulnerabilities while supporting the economic recovery.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet